The Effect of Generational Diversity, Rewards, Recognition, and Work Loyalty on Employee Job Satisfaction: Rewards, Recognition, and Employee Satisfaction - Zuzan Titi Ardian; Novita Ana; Ratna Wardani (Innovative Approaches in Health Science Journal, 2026)
Background: Employee job satisfaction is an important factor in maintaining service quality and the sustainability of hospital organizations. Good job satisfaction can improve performance, loyalty, and employee attachment to the organization. In a multigenerational hospital work environment, job satisfaction is influenced by various organizational factors, including generational diversity, rewards, recognition, and work loyalty. Methods: This study aims to analyze the effect of generational diversity, rewards, recognition, and work loyalty on employee job satisfaction at Gatoel Hospital in Mojokerto. This study uses a quantitative cross-sectional design. The population consists of all medical and non-medical employees at Gatoel Hospital in Mojokerto, totaling 359 people, with a sample of 186 respondents using simple random sampling. Bivariate data analysis used Pearson's correlation test. Multivariate analysis used multiple linear regression. Results: The results of the bivariate analysis showed that generational diversity influenced employee job satisfaction (p = 0.000; r = 0.512), rewards influenced employee job satisfaction (p = 0.000; r = 0.720), recognition affected employee job satisfaction (p = 0.000; r = 0.757), and work loyalty affected employee job satisfaction (p = 0.000; r = 0.759). The results of the multivariate analysis show that all variables simultaneously affect employee job satisfaction (p = 0.000), with work loyalty as the most dominant variable (β = 0.378). The coefficient of determination (Adjusted R² = 0.685) shows that generational diversity, rewards, recognition, and work loyalty explain 68.5% of the variation in employee job satisfaction. Conclusion: Generational diversity, rewards, recognition, and work loyalty significantly influence employee job satisfaction at Gatoel Hospital in Mojokerto. Among these factors, work loyalty emerged as the most dominant predictor. These findings highlight the importance of integrated human resource management strategies that strengthen organizational loyalty, ensure fair reward systems, and foster recognition across generational groups to enhance employee job satisfaction and support hospital sustainability.